Efficient Crack Length Measurement Using A* Shortest Path Methodology for a Phase-Field Fracture Framework - Vale, Matheus Garcia Do; Díaz, Julián Arnaldo Ávila [UNESP]; Boldrini, José Luiz; Bittencourt, Marco Lúcio (FapUNIFESP (SciELO), 2023)
Accurately measuring a crack length is a crucial aspect of experimental fracture tests. In this work, we present an innovative application of the A* (A-star) shortest path methodology to track different shapes of cracks from numerical simulations. This approach is highly efficient, significantly improving the speed and accuracy of crack length measurements. Furthermore, we introduce a modified weight cost function that follows the crack path in the damage field, enhancing the accuracy of our method. The effectiveness of the proposed procedure is shown by fabricating damage fields with different geometry and good agreement when compared to the exact values. In addition, we evaluate a time-dependent crack propagation case, achieving high accuracy. We present all features and steps of the procedure to showcase its efficacy in accurately measuring the length of a crack path. Finally, we validate our method using a phase-field fracture framework and compare it with the compliance technique. The results show that the proposed method is applicable in finite element analyses with recovering accurate results.
Keywords: A-Star; Crack length; Phase Field; Shortest-Path